Influence of wire feed rate on microslit width fabricated by wire ECM process. (9th July 2019) - Debnath, S.; Kundu, J.; Bhattacharyya, B.
Miniaturisation of metallic structures has become a prime issue and to meet high demand, modern fabricators extensively use different micro machining techniques. Wire electrochemical machining (wire ECM) is such a process of removing excess material electrochemically. However, the process is still new and further research is needed. Hence, the present work aims in developing suitable wire ECM setup to find out the influence of wire feed rate at varying voltage settings on corresponding width of the generated microslits. For this, experimentations have been carried out with 50 μm dia tungsten wire and machined micro features have been carefully observed under optical microscope. Additionally, the experimental results have been represented graphically where the minimum average width of the microslit is found to be 83.117 μm with an aspect ratio of 1.2. Moreover, complex microfeature with varying width has been fabricated by changing corresponding feed values in a single run.